Museums and sites of persuasion
1 online resource (1 volume)
Keywords: Museums and Sites of Persuasion examines the concept of museums and memory sites as locations that attempt to promote human rights, democracy and peace. Demonstrating that such sites have the potential to act as powerful spaces of persuasion or contestation, the book also shows that there are perils in the selective memory and history that they present. Examining a range of museums, memorials and exhibits in places as varied as Burundi, Denmark, Georgia, Kosovo, Mexico, Peru, Vietnam and the US, this volume demonstrates how they represent and try to come to terms with difficult histories. As sites of persuasion, the contributors to this book argue, their public goal is to use memory and education about the past to provide moral lessons to visitors that will encourage a more democratic and peaceful future. However, the case studies also demonstrate how political, economic and social realities often undermine this lofty goal, raising questions about how these sites of persuasion actually function on a daily basis. Straddling several interdisciplinary fields of research and study, Museums and Sites of Persuasion will be essential reading for those working in the fields of museum studies, memory studies, and genocide studies. It will also be essential reading for museum practitioners and anyone engaged in the study of history, sociology, political science, anthropology and art history.